Identification of the Elements and Systematisation of the Pillars of Solid Waste Management - Espuny, Maximilian [UNESP]; Costa, Ana Carolina Ferreira [UNESP]; Reis, José Salvador da Motta; Barbosa, Luís César Ferreira Motta; Carvalho, Raquel; Santos, Gilberto; de Oliveira, Otávio José [UNESP] (Technical University of Kosice, 2022)
Purpose: This study identifies elements and systematises them into pillars based on relevant scientific publications on the subject, highlighting actions that contribute to the public authorities and private organisations for developing Solid Waste Management (SWM), contributing to environmental, social, and economic sustainability. Methodology/Approach: This research used the content analysis method with the aim of identifying the main elements of SWM. To this end, the inductive approach was used to classify in a logical and organised manner the elements identified in the literature and then systematise them into pillars. Findings: The pillars identified in SWM were: Public Management, Public Policies, Environmental Solutions and Triple Bottom Line. Research Limitation/Implication: The main limitation of the study is the use of articles between the periods 2014 and 2018. Originality/Value of paper: The main scientific contribution was to expand and deepen the literature on the subject, articulating concepts in pillars that can be developed and improved according to the characteristics of different regions or localities, improving the use of SWM resources. As to the applied contribution, it was possible to analyse the fields of direct and indirect action of public and private sectors that can be implemented in SWM, improving the understanding of the limits that each stakeholder can contribute to the effectiveness of SWM. Category: Literature review
Keywords: content analysis; solid waste management; stakeholder engagement; sustainability